2013
DOI: 10.3171/2013.1.jns12743
|View full text |Cite
|
Sign up to set email alerts
|

Foramen ovale puncture, lesioning accuracy, and avoiding complications: microsurgical anatomy study with clinical implications

Abstract: F oramen ovale puncture was first described by Här-tel in 1914 18 as a percutaneous route to the Meckel cave to treat trigeminal neuralgia. Microvascular decompression induces little or no hypesthesia and is usually the treatment of choice for young patients without comorbidities.3 However, less invasive techniques, including FO puncture, are preferred Object. Foramen ovale (FO) puncture allows for trigeminal neuralgia treatment, FO electrode placement, and selected biopsy studies. The goals of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 48 publications
(62 reference statements)
1
45
0
Order By: Relevance
“…Much effort has been devoted to improving visualization and navigation to the foramen ovale. 89 Although fluoroscopy has been the imaging modality of choice, newer studies have demonstrated the potential usefulness of computed tomography, Dynacomputed tomography, and neuronavigation systems, especially for patients with anatomic variants that may prevent successful access with traditional means. [90][91][92][93] In 1 study of RFT, guidance with computed tomography fluoroscopy allowed for successful engagement of the foramen ovale on the first attempt, all requiring less than 40 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Much effort has been devoted to improving visualization and navigation to the foramen ovale. 89 Although fluoroscopy has been the imaging modality of choice, newer studies have demonstrated the potential usefulness of computed tomography, Dynacomputed tomography, and neuronavigation systems, especially for patients with anatomic variants that may prevent successful access with traditional means. [90][91][92][93] In 1 study of RFT, guidance with computed tomography fluoroscopy allowed for successful engagement of the foramen ovale on the first attempt, all requiring less than 40 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison our results against population data provided by Hwang et al (2005), Onswuke et al (2010), Ambica et al (2012) and Peris-Celda et al (2013) showed that our measurements are significantly different from other populations. The results of these studies are summarized in Table II below.…”
Section: Discussionmentioning
confidence: 82%
“…The abducens and trochlear nerves can be damaged by rhizotomy instrumentation and penetration into the temporal lobe or brainstem can also occur [20]. Reviewing cadaveric studies can help guide against these complications [15].…”
Section: Discussionmentioning
confidence: 99%
“…The risk for serious injury to adjacent neural and vascular structures from aberrant placement of the percutaneous trigeminal cannula must be considered [15][16][17][18]. Many complications have been reported after percutaneous balloon rhizotomy, but the most frequent are masticatory muscle weakness and dysesthesias, both of which typically improve in the postoperative period [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation